2011
DOI: 10.1007/s11010-011-0756-y
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB mediates the induction of Fas receptor and Fas ligand by microcystin-LR in HepG2 cells

Abstract: Microcystin-LR (MC-LR) is the most frequent and most toxic microcystin identified. This natural toxin has multiple features, including inhibitor of protein phosphatases 1 and 2A, inducer of oxidative stress, as well as, tumor initiator and promoter. One unique character of MC-LR is this chemical can accumulate into liver after contacting and lead to severe damage to hepatocytes, such as apoptosis. Fas receptor (Fas) and Fas ligand (FasL) system is a critical signaling system initiating apoptosis. In current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Transcription factor nuclear factor‐kappa B (NF‐κB), which is sensitive to ROS production and oxidative stress, is thought to play a key role in the development of several liver diseases including hepatitis, liver fibrosis and cirrhosis, and hepatocellular carcinoma (Sun and Karin, ; Morgan and Liu, ). Recent studies have reported that MC‐LR induced activation of NF‐κB in HepG2 cells (Feng et al, ), rat insulinoma cells (INS‐1) (Ji et al, ), melanoma cells (MDA‐MB‐435) (Zhang et al, ), human hepatoma cells (Huh7) (Christen et al, ), mice hepatocytes (Zhang et al, ), and HeLa cells (Chen et al, ). MC‐LR promoted nuclear translocation and activation of p65 subunit of NF‐κB, resulting in cellular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor nuclear factor‐kappa B (NF‐κB), which is sensitive to ROS production and oxidative stress, is thought to play a key role in the development of several liver diseases including hepatitis, liver fibrosis and cirrhosis, and hepatocellular carcinoma (Sun and Karin, ; Morgan and Liu, ). Recent studies have reported that MC‐LR induced activation of NF‐κB in HepG2 cells (Feng et al, ), rat insulinoma cells (INS‐1) (Ji et al, ), melanoma cells (MDA‐MB‐435) (Zhang et al, ), human hepatoma cells (Huh7) (Christen et al, ), mice hepatocytes (Zhang et al, ), and HeLa cells (Chen et al, ). MC‐LR promoted nuclear translocation and activation of p65 subunit of NF‐κB, resulting in cellular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these toxins have been linked with human and animal acute hepatotoxicity [26,27]. MC-LR can induce toxic effects in mammals [28,29], birds [30], and aquatic animals [31,32]. Moreover, some studies state that MCs can be transferred along food chain [33], suggesting a potential risk for human consumption of contaminated food products.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of MC potential carcinogenic activity is the inhibition of protein phosphatases (PP1 and PP2A), which influences the regulation of cellular protein hyperphosphorylation [41], thereby leading to cytogenetic and tumorigenic effects [42,43], or promotion of liver cell necrosis [44]. Recently, MC toxicity and carcinogenesis mechanisms have received great attention [2,13,29,[45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that the mechanism of MC-LR-induced hepatocyte apoptosis is thought to include the involvement in oxidative stress [3,7]. In addition, NF-κB mediates cellular apoptosis by MC-LR in HepG2 cells [8]. When human melanoma cells are exposed to exceptionally high concentrations of the toxins, binding to the ATP synthetase subunit could be a trigger of mitochondrial apoptotic signaling through perturbation of mitochondrial functions, with possible leakage of cytochrome [9].…”
Section: Introductionmentioning
confidence: 99%